D2D Communications Underlaying Wireless Powered Communication Networks - Wang, Haichao; Wang, Jinlong; Ding, Guoru; Han, Zhu (IEEE transactions on vehicular technology, 2018)
In this correspondence paper, we investigate the resource allocation problem for D2D communications underlaying wireless powered communication networks, where multiple D2D pairs harvest energy from a power station equipped with multiple antennas and then transmit information signals simultaneously over the same spectrum resource. The aim is to maximize the sum throughput via joint time scheduling and power control, while satisfying the energy causality constraints. The formulated nonconvex problem is first transformed into a nonlinear fractional programming problem with a tactful reformulation. Then, by leveraging difference of two convex functions programming, a suboptimal solution to the nonconvex problem is obtained by iteratively solving a sequence of convex problems. Simulation results demonstrate that the proposed scheme works well in different scenarios and can significantly improve the system throughput compared with the-state-of-the-art schemes.